The intimate universal : the hidden porosity among religion, art, philosophy, and politics - Desmond, William, 1951- (Insurrections., 2016)
William Desmond sees religion, art, philosophy, and politics as essential and distinctive modes of human practice, manifestations of an intimate universality that illuminates individual and social being. They are also surprisingly permeable phenomena, and by observing their relations, Desmond captures notes of a clandestine conversation that transforms ontology.